"Tumbuh setelah Bencana" - Rahman, Fadly (Jurnal Sejarah, 2019)
In Indonesian history, volcanic disasters are both disastrous and blessing. In the short term it becomes disastrous when the impact causes massive damage and takes many casualties. But in the long term it can becomes blessings because the ashes from volcanic eruptions has the potential to fertilize the soil. Volcanic disasters as happened in several parts of Dutch East Indies regions that were traversed by the "ring of fire" have attracted the attention of scholars, such as botanists Verbeek (1886), Treub (1888), Hemsley (1888 & 1903), Valeton (1905), Ernst (1907), Backer (1929); volcanologist ter Braake (1945); and agronomist Mohr (1945) in examining soil conditions post-eruption which is good to growth of various vegetations. From their research it was concluded that the regions with the highest number of active volcanoes tend to have a high level of soil fertility. This article discusses the traces of scientific researchs on the vegetation condition after eruption of Krakatoa (1883) and how the research results became guidance for the botanical study in Dutch East Indies on the last of 19th century until the first half of 20th century.